Asymmetric Alkoxy‐ and Hydroxy‐Carbonylations of Functionalized Alkenes Assisted by β‐Carbonyl Groups. Issue 32 (2nd July 2021) - Ren, Xinyi; Wang, Zhen; Shen, Chaoren; Tian, Xinxin; Tang, Lin; Ji, Xiaolei; Dong, Kaiwu
Abstract: As a fundamental type of carbonylation reaction, the alkoxy‐ and hydroxy‐carbonylation of unsaturated hydrocarbons constitutes one of the most important industrial applications of homogeneous catalysis. However, owing to the difficulties in controlling multi‐selectivities for asymmetric hydrocarbonylation of alkenes, this reaction is typically limited to vinylarenes and analogues. In this work, a highly efficient asymmetric alkoxy‐ and hydroxy‐carbonylation of β‐carbonyl functionalized alkenes was developed, providing practical and easy access to various densely functionalized chiral molecules with high optical purity from broadly available alkenes, CO, and nucleophiles (>90 examples, 84–99 % ee ). This protocol features mild reaction conditions and a broad substrate scope, and the products can be readily transformed into a diverse array of chiral heterocycles. Control experiments revealed the key role of the β‐carbonyl group in determining the enantioselectivity and promoting the activity, which facilitates chiral induction by coordination to the transition metal as rationalized by DFT calculations. The strategy of utilizing an innate functional group as the directing group on the alkene substrate might find further applications in catalytic asymmetric hydrocarbonylation reactions. Abstract : An efficient asymmetric alkoxy‐ and hydroxy‐carbonylation of β‐carbonyl functionalized alkenes was developed, providing practical and easy access to various densely functionalized chiral molecules with high optical purity. Control experiments revealed the key role of the β‐carbonyl group in determining the enantioselectivity and promoting the activity as rationalized by DFT calculations.